Role of Chemical Components of cork on Sorption of Aqueous Polycyclic Aromatic Hydrocarbons - Environ, J. (International Journal of Environmental Research, 2013)
In order to know the environmental behaviour of toxic pollutants it is fundamental to understand the role of chemical components of a material on sorption of such pollutants.In this study, the sorption of a mix of polycyclic aromatic hydrocarbons (PAHs) by cork fractions (i.e. raw cork (CF), free extractive cork (FEF) and nonsaponifiable (DESF)) has been investigated to better understand the role of biopolymers and extractable fraction of cork on their sorption behaviour. All samples were analyzed through elemental analysis and were examined using Fourier transform infrared spectroscopy. After removing the extractable fraction and the suberin from the cork, the sorption capacities (Koc ) of FEF and DESF exhibited mean reductions of 70% and 30% respectively. In addition, the sorption results of three pairs of cork samples with different chemical content confirm that the extractable fraction serves as the major sorption medium for PAHs. Considering only low molecular weight PAHs positive correlations between Koc with Kow (R2 =0.70) and F number (R2 =0.65) were found, showing that these parameters are involved in this adsorption process
Keywords: biopolymers; Cork; extractable fraction; organic pollutants; PAHs

The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna (Journal of Environmental Science and Health, Part A, 2011)
The aim of this study is to determine the sorption-desorption behavior of a mixture of thirteen aqueous PAHs on cork waste at a particle of size 0.25?0.42 mm obtained from the remains of cork strips. The final purpose is to use this natural adsorbent as an alternative to activated carbon in an innovative approach for the removal of this class of toxic compounds, and significantly reduce the regeneration costs of the process. The chemical composition of the selected cork revealed that suberin (38.5 %) and lignin (31.6 %) were the main structural components of the cell wall. The high efficiency of cork as a biosorbent of PAHs is shown by the fact that just over 80 % of adsorption occurred during the first two minutes of contact time. Both Freundlich's and Langmuir's isotherms gave good fits to the sorption process. The highest adsorption affinities were exhibited for pyrene, anthracene, and phenanthrene. Desorption studies indicate a high degree of irreversibility for all PAHs, and especially so in the case of high molecular PAHs. The correlation with KF and low molecular weight PAHs was the most significant. The quantity of cork required to reduce water pollution was estimated to be between 3 and 15 times less than the quantities required in the case of other materials (i.e. aspen wood and leonardite). This study demonstrates for the first time that cork is a potential biosorbent for PAHs and may have relevance in the future treatment of PAH-contaminated waters.
From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)From Duplicate 1 (The use of cork waste as a biosorbent for persistent organic pollutants–Study of adsorption/desorption of polycyclic aromatic hydrocarbons - Olivella, Maria À; Jové, Patrícia; Oliveras, Anna)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 21644164
Keywords: Adsorption; Aromatic; Aromatic: chemistry; biosorbent; Chemical; Chemical: chemistry; Cork waste; Environmental Remediation; Environmental Remediation: methods; Gas Chromatography-Mass Spectrometry; Lignin; Lignin: chemistry; Lipids; Lipids: chemistry; organic pollutants; PAHs; Polycyclic Hydrocarbons; Quercus; Quercus: chemistry; Solid Phase Microextraction; sorption-desorption; Time Factors; Water Pollutants; water treatment